Some Factors Affecting the In Vitro Culture of Banana (Biological Sciences - PJSIR, 2006)
Factors affecting in vitro regeneration of shoots in shoot tip explant cultures of banana cultivar ‘Basrai’, such as solid and liquid media, growth regulators, vitamins, and antioxidants were studied. Three-quarters strength of MS liquid medium supplemented with 17.75 mM 6-benzyladenine (BA), 11.42 mM indole-3-acetic acid (IAA) and 205 mM adenine sulphate induced the formation of mean number of 12.3 shoots, with the mean length of 3.0 cm, after three weeks of culture. Maximum shoot multiplication (14.33) occurred in liquid medium containing 22.19 mM BA. Addi- tion of 2.0% activated charcoal (AC) to the liquid medium improved quality of the regenerated plants with expanded and glossy leaves, though the number of shoots was reduced (13.66). Profuse formation of roots was characteristically induced by AC. Addition of citric acid (CA) to the medium caused decline in morphogenetic expression of the cultures.